Interferon alfa-2a therapy for a child with blue rubber-bleb nevus syndrome. - Bonduel, M.; Torres, A.F.; Hepner, M.; Cordisco, M.R.; Pierini, A. (European Journal of Pediatric Dermatology, 2018)
We describe a 1-month-old girl with Blue Rubber-Bleb Nevus Syndrome, a rare condition in which multiple venous malformations in the skin are associated with similar gastrointestinal lesions. She presented severe intestinal bleeding without response to corticosteroids. She received interferon alfa-2a 3 million U/m2 per day for a 6-month-period with a good clinical and laboratory evolution.